What we know about expectancy-value theory, and how it helps to design a sustained motivating learning environment. (November 2019) - Loh, Elizabeth K.Y.
Abstract: The expectancy-value theory (EVT) is widely used to explain and predict students' learning performance, persistence and aspirations. However, very few studies have examined how expectancy and subjective task values, the two constructs derived from the theory, are related to second language (L2) learning, and how the theory can be applied to daily teaching for the improvement of students' learning. Considering the rapid increase in the number of L2 students around the world, this article aims to propose possible ways to apply the EVT to daily L2 teaching and learning, as well as to create an optimal and sustained learning environment for the students, by reviewing the development of EVT and important studies related to L1 and L2 learning. Suggestions for new directions for future research are also provided.